Contribution of Cytosine‐Containing Cyclobutane Dimers to DNA Damage Produced by Photosensitized Triplet–Triplet Energy Transfer. Issue 19 (25th March 2014) - Douki, Thierry; Bérard, Izabel; Wack, Aude; Andrä, Sigrid
Abstract Mutagenic cyclobutane pyrimidine dimers (CPDs) can be induced in DNA through either direct excitation or photosensitized triplet–triplet energy transfer (TTET). In the latter pathway, thymines are expected to receive the excitation energy from the photosensitizer and react with adjacent pyrimidines. By using state‐of‐the art analytical tools, we provide herein additional information on the formation of cytosine‐containing CPDs. We thus determined the yield of all possible CPDs upon TTET in a series of natural DNAs with various base compositions. We show that the distribution of CPDs cannot be explained only by excitation of individual thymines. We propose that the mechanism for TTET involves at least dinucleotides as the minimal targets. The observation of the formation of cytosine–cytosine CPDs also suggests that additional pathways are involved in this photosensitized reaction.